Strengthening community’s Immunity Through people’s Participation to Develop the Community Regulation in Nakornping Sub-District; Chiang Mai Province - นุเสน, พะเยา (Ganesha Journal, 2019)
The objectives of this quantitative research were to 1) study the social factors that supported the preservation of the community’s culture and 2) study the community’s satisfaction towards community participation in establishing community regulations. The data were collected by having 535 community members, who were over 18 years of age, do a questionnaire. In selecting the participants, the researcher used Taro Yamane’s sample size formula and volunteer sampling technique. The data were collected and analyzed in terms of mean, percentage and standard deviation. The research results revealed that the social factor that helped preserve the community’s culture was the community’s informal regulation which controlled, managed and helped maintain the community’s culture. The samplings rated the process of community participation in establishing the community regulation excellent in every topic.